The red coral deposits of the Graham Bank area: Constraints on the Holocene volcanic activity of the Sicilian Channel. (June 2017) - Lodolo, E.; Sanfilippo, R.; Rajola, G.; Canese, S.; Andaloro, F.; Montagna, P.; Rosso, A.; Macaluso, D.; Geronimo, I. Di; Caffau, M.
Abstract: The Graham Bank is a broad and relatively shallow relief located off the SW coast of Sicily. This area hosts, among other submarine edifices, the ephemeral Ferdinandea Island, created in 1831 by an explosive eruption - the only well-documented event occurred in the study area - and rapidly dismantled by erosional processes. In the Graham Bank and its vicinity, three red coral deposits have been discovered and extensively exploited commercially during the last part of the 19th century, and were quickly depleted after discovery, since no living coral populations survived or repopulated the area after geological events that caused the massive die off. The coral deposits lay on a muddy sea-floor alongside some volcanic reliefs, and consisted of mostly dead corals, intermingled with volcanic and biogenic debris. Here, we describe these deposits and propose a model for their evolutionary history through palaeoecological analyses of their faunistic content, radiocarbon dating, Remotely Operated Vehicle sea-floor observations, and seismic profiles. Overall presented data suggest that these deposits have accumulated primarily (or even partially) as a consequence of volcanic activity dislodging living (or dead) corals from the steep flanks of volcanoes on which they lived. Periodic collapses of the friable pyroclastic walls of these edifices and landslides may have been triggered by repeated submarine eruptions, possibly associated with small earthquakes.